Fysiologia, psykologia ja kokeellisen sielutieteen tulo Suomeen. - Aho, Jouko (1989)
Physiology and the beginning of the experimental psychology in Finland.
Summary: Physiology and the beginning of the experimental psychology in Finland.
Keywords: psykologia; kokeellinen psykologia; historia; psykologi; experimentell psykologi; historia; Suomi; Finland